Winner! winner! chicken dinner : 50 winning ways to cook it up! - Billis, Stacie (North Adams, MA : Storey Publishing, 2020)
"Home cooks can prepare delicious chicken suppers with confidence and ease. Each chapter is chock-full of tips and tricks that use a wide range of techniques, from braising and roasting to grilling, slow cooking, and sheet-pan cooking"--
Choosing, buying & handling -- Butchering & carving for the everyday cook -- Recipes. In an oven: roasting & baking ; In a pan: sauteing, stir-frying & braising ; In a pot: stewing, frying & under pressure -- On a grill: burgers & wings -- Using & creating leftovers.
Includes index.
108920
Keywords: Cooking (Chicken); Cookbooks